Pengaruh Kualitas Pelayanan, Produk dan Promosi terhadap Keputusan Pembelian Produk Sari Roti di Kecamatan Karya Penggawa Kabupaten Pesisir Barat - Yani Setyawati; Roy Saga; Ahmad Badrid Dujya; Fathan Nabawiyal Amni (Universitas Bumigora, 2021)
This study aims to determine the effect of service quality, product, and promotion on purchasing decisions for Sari Roti products in Karya Penggawa District, Pesisir Barat Regency. The sample of this research is 60 respondents who have filled out the questionnaires that have been distributed. Data analysis using validity test, reliability test, and hypothesis testing. The drawback of this research is that it only gets a few respondents. The hope for further research is to increase the number of respondents. The test results show that the quality of services, products, and promotions is highly approved and in great demand among the public.